Evaluation of the trends and outcomes for women screened for and diagnosed with cervical precursor lesions: A Western Australian perspective - Munro, Aime (Curtin University, 2015)
Background - Specific questions regarding the management of cervical cancer precursor lesions still exist. Aims - Identify areas for improvement in the management of cervical abnormalities. Methods - A retrospective population-based cohort study was conducted for women diagnosed with a low-grade glandular or a high-grade cervical lesion. Conclusion - Findings support the revision of management guidelines supported by educational sessions would improve the efficacy of conservative treatment modalities and the importance of post-treatment surveillance.